Natural Antioxidants and Biocides from Wild Medicinal Plants - Céspedes, Carlos L (CABI, 2014)
The current book provides an up-to-date treatment of antioxidant and biocidal compounds mainly from Latin American plants. New antimicrobials, insecticides and antioxidants are compiled in a single source for the first time based on the research and knowledge of several internationally renowned research groups. The book is organized in three sections: Part I provides a general overview and perspectives on antioxidant, medicinal and biocidal plant compounds; Part II provides information on plant antioxidants isolated from a wide range of species; and Part III describes insecticidal, antimicrobial and other biocidal activities based on peptides, phytoecdysteroids, alkaloids, polyphenols, terpenoids and other allelo- chemicals. This book will be a helpful reference for students, researchers and teachers interested in allelochemistry as well as the antioxidant and medicinal properties of Latin American plants.